Tolypocladium rhizomatum sp. nov.: an endophytic species isolated from the rhizome of Polygonatum cyrtonema - Chen, Ming-Jun; Han, Yi-Ren; Hu, Jiang-Xin; Liu, Yu-Jun; Huang, Bo (Phytotaxa, 2023)
Tolypocladium is a diverse group of asexual or sexual fungi within the Ophiocordycipitaceae family, exhibiting a diverse range of hosts, living habits and geographical distribution. In this study, a Tolypocladium strain RCEF6720 was isolated from the rhizome of Polygonatum cyrtonema, collected in Huangshan City, Anhui Province, China. Phylogenetic analyses of multiple loci (ITS, SSU, LSU, TEF1-α and RPB1) indicated that the strain RCEF6720 was clustered with other Tolypocladium species associated with plant habitats, including T. album, T. amazonense, T. endophyticum and T. tropicale. Further study revealed that the strain RCEF6720 was identified as a distinct lineage, separated from T. album. While the strain’s morphological characteristics resemble those of T. album, it is distinguished by longer phialides. Based on the combination of its unique morphological characteristics and phylogenetic placement, the strain is proposed as a new species, named Tolypocladium rhizomatum sp. nov.